Mathematical Reasoning Ability of Junior High School Students Through Problem Based Learning Model with Ethnomathematical Nuance - Maidiyah, Erni; Anwar, Nadia; Mailizar, Mailizar; Zaura, Bintang; Suryawati, Suryawati; Harnita, Fahlida (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2021)
Utilization of ethnomathematics which is part and one of learning with a contextual approach is expected to maximize students' mathematical reasoning abilities in learning mathematics. The purpose of this study was to determine the increase in students' mathematical reasoning abilities taught by the PBL model with ethnomathematical nuances. This research was an experimental study with a control group design pre-test-post-test. The research instrument used was a test of mathematical reasoning abilities. Data were analyzed using t-test. The experimental class experienced better mathematical reasoning abilities than the control class. This can be seen from the N-Gain average value of the experimental class of 0.54 with moderate criteria but the control class of 0.24 with low criteria. Based on the results of hypothesis testing, H1 was accepted, namely the increase in mathematical reasoning abilities of students who received learning with the ethnomatic nuanced PBL model better than students who received conventional learning.Pemanfaatan etnomatematika yang merupakan bagian dan salah satu pembelajaran dengan pendekatan kontekstual diharapkan dapat memaksimalkan kemampuan penalaran matematis siswa dalam pembelajaran matematika. Tujuan penelitian ini adalah untuk mengetahui peningkatan kemampuan penalaran matematis siswa yang diajar dengan model PBL bernuansa etnomatematika. Penelitian ini merupakan penelitian eksperimen dengan desain kelompok kontrol pre-test-post-test. Instrumen penelitian yang digunakan adalah tes kemampuan penalaran matematis. Data dianalisis menggunakan uji-t. Kelas eksperimen mengalami kemampuan penalaran matematis yang lebih baik daripada kelas kontrol. Hal ini terlihat dari nilai rata-rata N-Gain kelas eksperimen sebesar 0,54 dengan kriteria sedang tetapi kelas kontrol sebesar 0,24 dengan kriteria rendah. Berdasarkan hasil pengujian hipotesis, H1 diterima yaitu peningkatan kemampuan penalaran matematis siswa yang mendapat pembelajaran dengan model PBL bernuansa etnomatik lebih baik daripada siswa yang mendapat pembelajaran konvensional.